Empirical modelling of sugar uptake and water desorption of osmotically dehydrated mango (Mangifera indica L. cv. Carabao) slices - Imbong, Louis Alain Balios
Empirical models describing the sugar uptake and water desorption of mango (Mangifera indica L. cv. Carabao) slices as a function of soaking time were derived.